Forms of prejudice about christians and social cohesion between university students in Slovakia: media as an essential part of the issue - Tkáčová, Hedviga (Journal of Education Culture and Society, 2021)
Aim. The subject of our interest is to research the forms of prejudice about Christians among university students. Part of the research focuses on the question of the forms of prejudices of the research group in relation to religious classmates – peers and part of on significant influence of media on the negative perception of Christianity in the society. The reflection of the findings is a consideration of the decline in social cohesion due to (1) the existence of prejudices in the university environment in Slovakia, and (2) the often negative media presentation of Christian religion in the Slovak media. Concept. The starting point of the issue is the research into the forms of prejudice and the potential for social exclusion of young people due to the existence of prejudice in the university environment. The need for this kind of research and reasoning arises from growing fears and the strengthening of phobias that accumulate within the groups we observe. Results and conclusion. The reflection of the findings is a consideration of the decline in social cohesion due to (1) the existence of prejudices in the university environment in Slovakia, and (2) the often negative media presentation of Christian religion in the Slovak media. Cognitive value. Qualitative statements confirm the decline in social cohesion among peers due to religious diversity. We consider the presence of religious prejudices as an urgent call for such forms of education that would effectively contribute to the acceptance of cultural and religious diversity in society and to the promotion of social cohesion in the university environment.